Analisis Pengaruh Beban Dan Kecepatan Terhadap Penampang Gesekan Ban Pada Lintasan Beton - Agus Suprayitno; TB. Utami Adi Subekhi; Yadi Heryadi; Sandi Herdiana; Anwar, Choirul (Sekolah Tinggi Teknologi Wastukancana, 2023)
Abstract. Two-wheeled vehicles, namely motorbikes, are still the mainstay as an affordable means of transportation for the majority of Indonesian people. Motorcycles are a means of transportation that are often found, both in urban and rural areas. Motorcycles have many advantages compared to other means of transportation Tires are an important part of land vehicles, tire conditions that are not in accordance with the standards can cause tire bursts which result in traffic accidents. Frictional forces that occur in the tires can cause wear on the tires. Various factors that affect wear include the speed of movement and the amount of load. In this study an analysis was carried out to find out how the effect of load and speed on the resulting frictional cross-sectional area. The analytical method used in this study is Kruskall-Wallis and Mann-Whitney. Penelitian ini menghasilkan kesimpulan bahwa faktor beban memiliki pengaruh yang signifikan terhadap penampang gesekan ban sepeda motor pada lintasan beton. Sedangkan perlakuan atau faktor kecepatan tidak memiliki pengaruh yang signifikan terhadap penampang gesekan ban sepeda motor pada lintasan beton.